2003
DOI: 10.1046/j.1443-1661.2003.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐aided grading system for endoscopic severity in patients with ulcerative colitis

Abstract: The degree of mucosal redness can be quantified as an index of hemoglobin (IHB) that changes with photographic conditions. The first aim of the present study was to stress the exclusion of γ correction as a critical procedure for reliable measurements of IHB. The second aim was to characterize Matts grade by pictorial parameters in the gray scale picture of IHB and to establish a computer‐aided grading system of endoscopic severity in ulcerative colitis. A total of 130 digital endoscopic pictures of 55 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…CAD is a general term used for a variety of artificial intelligence techniques applied to interpretation of gray‐scale medical images, including mammogram or chest X‐ray radiogram for cancer screening 19 . We have previously reported a reliable image‐processing method to extract the morphological features for spatial arrangements of mucosal color 6 and the degree of mucosal surface roughness 7 . These quantitative methods are potential tools to improve reliability in image interpretation by minimizing interobserver variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAD is a general term used for a variety of artificial intelligence techniques applied to interpretation of gray‐scale medical images, including mammogram or chest X‐ray radiogram for cancer screening 19 . We have previously reported a reliable image‐processing method to extract the morphological features for spatial arrangements of mucosal color 6 and the degree of mucosal surface roughness 7 . These quantitative methods are potential tools to improve reliability in image interpretation by minimizing interobserver variation.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is quite easy for human observers to recognize and describe the features of the microvascular structure or spatial arrangements in empirical terms, it has been extremely refractory to get a precise definition and analysis by computers. Image processing method has been a useful means to quantify any element composing an endoscopic picture, including mucosal pattern (spatial arrangements of mucosal color) 6 or the degree of mucosal surface roughness 7 …”
Section: Introductionmentioning
confidence: 99%
“…We have previously established CAD for grading endoscopic severity in patients with ulcerative colitis [8] or CAD for detecting flat type early esophageal cancer [13]. In the present study, it has been demonstrated that CAD methods can be utilized as a means for an effective screening of gastric cancer by identifying the high risk population needing follow-up endoscopy.…”
Section: Discussionmentioning
confidence: 75%
“…The color of any object in the digitized picture can be quantified by the intensity of red (R), green (G) and blue (B) reflectance. As hemoglobin is the predominant chromophore in the gastrointestinal mucosa, a colorant endoscopic picture is equivalent to a grey scale picture with index of hemoglobin (IHB=32log2[R/G] ) assigned to each pixel ( Figure 2) [8]. The grey scale picture with blackout or halation excluded was processed for 4 basic statistical parameters (mean IHB, SD of IHB, skewness of IHB, kurtosis of IHB) and 11 textural features that are related with spatial arrangements of the grey scale intensities (Table 1) [10].…”
Section: Pictorial Features Of the Endoscopic Imagesmentioning
confidence: 99%
See 1 more Smart Citation